"I just couldn't step out of the circle. I was trapped": Patterns of endurance and distress in Chinese-Canadian women with a history of suicidal behaviour. (July 2016) - Zaheer, Juveria; Shera, Wes; Tsang, A. Ka Tat; Law, Samuel; Fung, Wai Lun Alan; Eynan, Rahel; Lam, June; Zheng, Xiaoqian; Pozi, Liu; Links, Paul S.
Abstract: Rationale: Recent studies have highlighted higher rates of suicidal ideation and behaviour and associated themes of gender role stress in Chinese women residing in North America. However, qualitative studies, which privilege their voices in the discourse of suicide prevention and provide insight into their experiences, are lacking. Objective: To gain an understanding of the life histories, patterns of distress and constructions of suicide of Chinese-Canadian women with a history of suicidal behaviour. Methods: Ten women were recruited from four mental health programs in Toronto, Canada and participated in qualitative interviewing and analysis informed by constructivist grounded theory. Results: Chinese-Canadian women describe experiencing "stress" or "pressure" leading to the exacerbation of depressive symptoms. Stress and pressure are managed through a coping strategy of endurance, informed by the cultural conception of "ren". Cultural influences contribute to the manifestation of stress and pressure as somatic symptoms and sleeplessness. Finally, the women describe feeling unable to endure through worsening distress, reaching a "breaking point"; suicidal behaviour is constructed as a strategy to disrupt this cycle. Conclusion: This study challenges the binary notion that suicidal behaviour is either a consequence of mental illness or a reaction to interpersonal stress. Rather, the women describe an ingrained pattern of enduring through psychosocial problems without acknowledging worsening anxiety, depressive and physical symptoms. The pattern of endurance also prevents early treatment of these difficulties, resulting in the intensification of symptoms until a breaking point is reached. Knowledge of these patterns and coping strategies can allow for earlier identification and intervention for women at risk to prevent the worsening of distress leading to suicidal thoughts and behaviour. Highlights: Chinese-Canadian women describe "stress" or "pressure", exacerbating depressive symptoms. Chinese-Canadian women deal with their stress and pressure by "ren" or "endurance". Cultural influences lead stress and pressure being manifest as somatic symptoms. They often seek treatment for insomnia rather than depression or suicidal ideation.